Institutional Ethical behavior of Nurses: A Qualitative Case Study at Budi Rahayu Catholic Hospital, Blitar - Mulyono, Artisari Tri; Suprapto, Sentot Imam; Suhita, Byba Melda (Universitas STRADA Indonesia, 2025)
Professional ethics governs the behavior of nurses in carrying out their responsibilities and maintaining the integrity of the nursing profession. This study aimed to explore the factors that influence nurses’ ethical behavior toward their institution at Budi Rahayu Catholic Hospital, Blitar. A qualitative case study design was employed. Seventeen implementing nurses were selected through purposive sampling based on predetermined inclusion criteria. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using the stages of data reduction, data presentation, and conclusion drawing. To ensure data validity, source triangulation was conducted with five head nurses and one head of the nursing division.